From Inclusion to Belonging: A Practical Theology of Community, Disability and Humanness - Swinton, John (Journal of religion, disability & health, 2012)
This article develops a perspective on a practical theology of belonging. It argues that the political rhetoric of inclusion, while possibly necessary, is deeply inadequate to help us understand what disability is and what it really means to be with people who have received this label. We need to shift our thinking from inclusion to belonging and to reframe our practices from politics to love. The article seeks to do three things. Firstly, it highlights that the term disability is a vague and complex concept that, while it might be necessary, requires to be treated with both caution and suspicion. Secondly, the article argues that the idea of including people with disabilities does not go far enough in overcoming the alienation, stigmatization, and exclusion of those whom we choose to name “disabled.” We need to move from ideas of inclusion to the practices of belonging. Finally, the article engages with the theologies of Jean Vanier and Dietrich Bonhoeffer and suggests that the key to such transformation is not in politics but in Jesus. It is only as we learn how to love one another in and through Jesus and to create communities that embody such Christ-like love that we can begin to understand what it means truly to belong.